Laboratory diagnosis of Trypanosoma cruzi infection: a narrative review - Lopez Albizu, Maria Constanza (2023)
Trypanosoma cruzi infection, currently endemic in 21 countries, is a public healthproblem not only in the Americas but also in countries with Latin Americanmigrants. However, it is estimated that two-thirds of people with Chagas diseasecurrently live in urban areas and that only 10% of them are aware of it. This reviewsummarizes the most important aspects of the diagnosis of human T. cruziinfection by describing the following aspects of clinical laboratory diagnosis: themost widely used tests available in Latin America and those expected to improveaccess to diagnosis of the affected population with their implementation; theadvantages, disadvantages, and sensitivity of the tests in the different phases ofinfection; and their usefulness in the acute or chronic phases of infection and inthe context of immunosuppression. In this way, we hope to contribute tobroadening the knowledge about this prevalent infection in the Americas.